In Utero Fetal Ovarian Torsion with Imaging Findings on Ultrasound and MRI - Ripple Sheth; Dennis Hoelzer; Emily Scattergood; Pauline Germaine (Case Reports in Radiology)
Early diagnosis of ovarian torsion is critical in avoiding complications and planning management. Therefore, it is important to understand and assess the imaging findings of ovarian torsion. Ultrasound is the imaging modality of choice; however, it is not always definitive and diagnosis can be challenging. MRI is a better imaging modality to evaluate for signs of complications and to arrive at a more definitive diagnosis. We present a case of in utero ovarian torsion diagnosed during routine prenatal ultrasound with imaging findings on ultrasound and MRI postnatally.